Preoperative computed tomography-guided soft hook-wire localization for multiple pulmonary nodules - Li, Guang-Chao; Wu, Zheng-Long; Shi, Yi-Bing; Wang, Jing-Ya; Fu, Yu-Fei (Frontiers in Oncology, 2025)
BackgroundWhile there have been prior reports on pulmonary nodule (PN) localization through computed tomography (CT)-guided soft hook-wire (SHW) placement, there remains a dearth of studies specifically focused on the CT-guided SHW localization of multiple PNs. This study was thus designed to specifically evaluate the efficacy and safety of this localization strategy in patients with multiple PNs.MethodsIn total, 43 consecutive patients with multiple PNs underwent CT-guided SHW localization followed by video-assisted thoracoscopic surgery (VATS) to resent these PNs in our hospital between January 2022 and December 2022. A control group consisting of 140 individuals who underwent the CT-guided SHW localization of a single PN during the same interval was also selected. Both groups were analyzed retrospectively for safety and efficacy outcomes.ResultsThe final study population included 43 patients (94 PNs) in the multiple PN group, and 140 patients (140 PNs) in the single PN group, with all patients having undergone CT-guided SHW localization of these PNs. A one-stage procedure was employed for the localization of multiple PNs. The respective rates of technical success for SHW localization in the multiple and single PN groups were 98.9% and 100% (P = 0.402). The duration of localization in the multiple PN group was significantly longer than that in the single PN group (P = 0.001). The respective pneumothorax rates in the multiple and single PN groups were 32.5% (14/43) and 15.7% (22/140) (P = 0.015), while the corresponding lung hemorrhage incidence rates were 48.8% (21/43) and 36.4% (51/140) (P = 0.145). All PNs successfully underwent limited VATS resection, with a one-stage VATS procedure having been used for the resection of multiple PNs in a given patient.ConclusionsCT-guided SHW localization is a safe and effective means of localizing multiple PNs in a single patient. This simultaneous localization of multiple PNs can provide effective guidance for the subsequent one-stage limited VATS resection of these nodules.